3-Year Follow-Up of Nonextraction Crowded Cases Treated With the Damon System - Faruk Ayhan Başçiftçi; Zeliha Müge Baka; Sinem Bayram; Emire Aybüke Erdur (Turkish Journal of Orthodontics, 2014)

(untitled)
Objective:The aim of this retrospective study was to investigate treatment efficiency and 3-year follow-up stability of the Damon system by evaluating peer assessment rating (PAR) index, posteroanterior-lateral cephalometric changes, and the intercanine and intermolar widths.Materials and Methods:Fifty-five patients treated with a 0.022-inch slot Damon D3 MX bracket system were evaluated in this study. Cephalometric radiographs, dental models, and PAR scores were measured and evaluated pretreatment (T1), posttreatment (T2), and 3 years after treatment (T3). Repeated-measures analysis of variance (ANOVA)/paired t test were performed to evaluate the differences between the periods.Results:The mean PAR score of 34.75 at T1 was reduced to 3.35 and 3.05 at T2 and T3, respectively, succeeding in a 90.35% reduction with treatment. At T1–T2 and T1–T3, maxillary intercanine and intermolar width and mandibular intercanine width increased significantly. Although intercanine and intermolar widths decreased in both arches at T2–T3, only maxillary intercanine width showed a small, but statistically significant decrease (0.09 mm, p=0.001). Value of SNB angle, Md1-NB (mm), Md1-NB (degrees), and E plane-lower lip increased significantly at T1–T2 and T1–T3. Therefore, treatment resulted in mandibular incisor and lower lip proclination. All of the posteroanterior cephalometric changes were statistically significant except facial width changes at T1–T2.Conclusions:This study represented satisfactory results and a good follow-up stability with the Damon system. The Damon system can be used for nonextraction treatment in patients with moderate crowding.